A positive legacy of trauma? A study on the impact of natural disasters on medical utilization. (4th July 2018) - Iqbal, Usman; Li, Yu-Chuan Jack; Tang, Kung-pei; Chien, Hui-Chen; Yang, Ya-Ting; Hsu, Yi-Hsin Elsa
Abstract: Objective: The impact of natural disasters on medical utilization is largely unknown and often overlooked how it affects bereaving and non-bereaving survivors. The aim of this study is to determine the medical utilization between both survivor groups and long-term effects. Study design: A 10-year 1999–2009 population-based retrospective study by using the National Health Insurance claim database and the Household Registration database from the Department of Health, Executive Yuan, Taiwan. Settings: Taiwan 1999 Chi-Chi earthquake-affected areas. Participants: A total of 49 834 individuals which included 1183 bereaving survivors and 48 651 non-bereaving earthquake survivors. Intervention(s): None. Main Outcome Measures: Medical utilization of bereaving and non-bereaving survivors. Results: The results showed that bereaving survivors had significantly more outpatient visits before the earthquake, within 3-month period and 1 year after earthquake (odds ratio (OR) = 1.11, 1.16 and 1.08). However, after 1 year after earthquake their outpatient visits were not significantly different from non-bereaving, and even significantly less in some years. Inpatient visits of bereaving survivors had similar trend to outpatient visits, i.e. visits were more both before earthquake and within 3-month period after earthquake (OR = 1.59 and 1.89), however, they were not significantly higher than non-bereaving survivors for the following years of the study. Conclusion: Our study reveals that compared to non-bereaving survivors, bereaving survivors slightly had higher medical utilization in the beginning stage of earthquake, i.e. for the first 3-month period or 1 year after earthquake. However, there were no differences between these two groups in medical utilization including outpatient and inpatient visits in long run.